Societies In Posttransition, Market Fundamentalism and Totalitarianism of the New Age - Kostić, Aleksandar V. (Sociološki pregled, 2019)
The author deals with the consequences arising from the controversy of neoliberal concept and market fundamentalism. He presented the problem of coincidences and differences that have deeper repercussions on societies in transition and the world in general. He explored the controversies of neoliberalism related to the way it creates mechanisms of power, capital accumulation, propaganda, and the use of various means to keep the concept alive. He points to the rigid approach of the Brussels administration, which extends to all aspiring countries. Market fundamentalism and pathological consumption are the two sides of neoliberalism. A large number of countries in transition have run into even greater problems, after implementing the directives of the International Monetary Fund and listening to the advice of foreign experts. The economic power of developed countries and the authoritarian approach are not only the result of economics but also of ideology or geostrategy. Inequality is steadily deepening. Blank forms are spreading and are accepted in all cultures. The author points out that global homogenization through “non-places” and “non-things”, with the help of “non-services”, in fact, abstracts man by promoting the power of market fundamentalism. It is a kind of template for the totalitarianism of the New Age.
Keywords: market fundamentalism; post-transition; non-places; capital; totalitarianism of the New Age